Artemisia taurica Willd. var. vanensis Kursat & Civelek (Asteraceae: Anthemideae), a new variety from Eastern Anatolia of Turkey - Kurşat, Murat; Cıvelek, Semsettin; Sancar, Pelin Yılmaz; Türkoğlu, İsmail (My University, 2018)
During our revisionary study on the taxa of the genus Artemisia L. (Asteraceae) distributed in Turkey, we cameacross two populations that we anticipated could be a new variety of the species Artemisia taurica Willd. belonging tothe subgenus Seriphidium (Besser) Fourr. In the morphological and cytological studies, we found that the new varietyshould be included in the species A. taurica but it also has some considerable morphological differences. Thesemorphological differences include the length of stems, peduncles, pistils, styles, forks of stigmas, stamens, filaments, anddimensions of leaves, phyllaries, corollas, ovaries, anthers, achenes, the direction of synflorescens branches, theorientation of the capitula on the synflorescens branches, colour of corolla, and the type of indumentum. The new varietywas also different in terms of chromosome number. Based on these differences, we suggested that a new variety of thespecies A. taurica should be described, as A. taurica var. vanensis which is only distributed in a very limited area in theEastern of Turkey. In this article, an identification key for all taxa in the subgenus Seriphidium and a rearrangeddescription of the species A. taurica for including its two varieties, a diagnosis and an identification key for two sistervarieties, a distribution map and a few descriptive figures of the new variety have been given.
Keywords: Biyoloji